1948
DOI: 10.1111/j.1749-6632.1948.tb27276.x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Lymphogranuloma Venereum and Granuloma Inguinale in Humans With Aureomycin

Abstract: a preliminary study which is in prcss,' IVC have reported results in Cmenty-five cases of lymphogranuloma venercum treated with Anreomycin. This study was conducted between January 22nd, 1948, and April 24th, 1948. The results obtained with this new therapeutic agent were so superior to all other forms of therapy2 that had been used by us that me did not hesitate to continue its use. In the earlier paper, it was stated that Aureomycin was used for the first time in human beings. Apparently we were dealing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1949
1949
1973
1973

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Streptomycin, terramycin, chloramphenicol, and aureomycin have all proved useful in actual practice, the dosage varying according to the duration of infection and the chronicity of the disease. Important observations regarding the potency of aureomycin are to be found in the work of Wright et al (1948), Hill et al (1949), and Wammock et al (1950. Further, Greenblatt et al (1950) reported good results using aureomycin by mouth in a series of 46 patients, five of whom had not responded to streptomycin.…”
Section: Discussi'onmentioning
confidence: 99%
“…Streptomycin, terramycin, chloramphenicol, and aureomycin have all proved useful in actual practice, the dosage varying according to the duration of infection and the chronicity of the disease. Important observations regarding the potency of aureomycin are to be found in the work of Wright et al (1948), Hill et al (1949), and Wammock et al (1950. Further, Greenblatt et al (1950) reported good results using aureomycin by mouth in a series of 46 patients, five of whom had not responded to streptomycin.…”
Section: Discussi'onmentioning
confidence: 99%
“…Neither aureomycin nor chloramphenicol is significantly virucidal in vitro. There is some evidence for the clinical effectiveness of aureomycin against psittacosis (95) and considerable data (96,97) which indicate a curative effect on acute lymphogranuloma venereum. Other antibiotics tested against Chlamydozoaceae and found to be inac tive include streptomycin as previously mentioned (75,76) bacitracin (73), and streptothricin (75).…”
Section: Virus and Rickettsial Infections 225mentioning
confidence: 99%
“…Successful clinical trials have been reported in a wide variety of bacterial and rickettsial infections, as well as infections due to lymphopathia venereum virus and the causative agent of primary atypical pneumonia (4,6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Toxic reactions have been few and insignificant.…”
mentioning
confidence: 99%